A Lattice Boltzmann Study of Phase Separation in Liquid-Vapor Systems with Gravity (Communications in Computational Physics, 2018)
Phase separation of a two-dimensional van der Waals fluid subject to a gravitationalforce is studied by numerical simulations based on lattice Boltzmann methodsimplemented with a finite difference scheme. A growth exponent α=1 is measured inthe direction of the external force.